Ethical issues in dialysis therapy. Issue 10081 (6th May 2017) - Jha, Vivekanand; Martin, Dominique E; Bargman, Joanne M; Davies, Simon; Feehally, John; Finkelstein, Fred; Harris, David; Misra, Madhukar; Remuzzi, Giuseppe; Levin, Adeera; ,
Summary: Treatment for end-stage kidney disease is a major economic challenge and a public health concern worldwide. Renal-replacement therapy poses several practical and ethical dilemmas of global relevance for patients, clinicians, and policy makers. These include how to: promote patients' best interests; increase access to dialysis while maintaining procedural and distributive justice; minimise the influence of financial incentives and competing interests; ensure quality of care in service delivery and access to non-dialytic supportive care when needed; minimise the financial burden on patients and health-care system; and protect the interests of vulnerable groups during crisis situations. These issues have received comparatively little attention, and there is scant ethical analysis and guidance available to decision makers. In this Health Policy, we provide an overview of the major ethical issues related to dialysis provision worldwide, identify priorities for further investigation and management, and present preliminary recommendations to guide practice and policy.